Clinicopathologic pattern and outcome of management of Pancreatic Carcinoma in Ibadan, Nigeria (2019)
Background: Pancreatic cancer is one of the most challenging tumor entities worldwide, characterized as a highly aggressive disease with dismal overall prognosis and an incidence rate equaling mortality rate. Objective: In order to have an up to date data on pancreatic cancer incidence and trend in Nigeria, West- Africa; we conducted an epidemiological analytical review of the pattern, management and management outcome of pancreatic cancer in Ibadan, Nigeria. Methods: We performed a retrospective hospital-based study in which we analyzed the records of 126 pancreatic cancer patients registered, evaluated and treated in the University College Hospital, Ibadan, a major referral tertiary Hospital in the South Western region of Nigeria, West African from January 1999 to January 2013.The data obtained include bio-data, clinical presentation, treatment and outcome which were analyzed with descriptive statistics using SPSS 22. Results: During the period of study, 126 patients were diagnosed with pancreatic cancer; with a mean age of 60.2 years, and a male to female ratio of 1.52:1; other parameters such as a medical history smoking and alcoholism history, tumor site; histological type as well as the stage of diagnosis were also enrolled in the study. Our statistical analyses reported a very significant correlation between patients who belonged to the age group of 30-45 years and the advanced stage of diagnosis (based on TNM classification) with P=0.02. Conclusion: Pancreatic cancer is increasingly diagnosed in young adults at an advanced stage in the West African sub-region. Most patients present with advanced condition only amenable to palliative measures. There are significant challenges in the area of diagnosis, screening, treatment and research. The role of public health campaign to educate the populace on the disease and early presentation cannot be overemphasized.